Pengaruh Pola Hidup Masyarakat terhadap Penyakit Diabetes Melitus di Desa Tengah Kecamatan Pantai Labu - Yusril Iza Mahendra; Yunia Humairah Ayub; Bintang Rizki Angeli; Suhaila Syahda; Annisa Hasanah; Wahyudi Wahyudi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Diabetes Mellitus (DM) is a chronic disease caused by a disturbance in the body, so that the body cannot produce or use blood glucose into the body's cells, resulting in glucose accumulating in the blood. Symptoms of diabetes are characterized by increased blood sugar which tends to be higher than normal. This study used quantitative research with cross sectional analysis method because this research was carried out at one time. The sample in this study was the elderly community in Tengah Village, Pantai Labu District, totaling 40 people. From the results of the research conducted, it shows that the residents or people in Tengah Village always adopt a healthy lifestyle, even the elderly. Because, we can see that researchers examined the community as many as 40 people. However, out of the 40 respondents, only 6 people had diabetes mellitus.